Design principles and problem authenticity of constructivist learning environments for secondary science education - Yeo, Jennifer Ai Choo. (2008)
Science is a human endeavour striving towards a better way of explaining scientific phenomena through experimental and theoretical investigations (Kuhn, 1970). The works of science is fundamentally situated and not objectively applied. However, traditionally, science learning involves learning a great deal of scientific facts through lectures and demonstration, only to apply these facts in well-structured problems.